Digital Nudging and Visit Intention Among Generation Z: Evidence from Scarcity and Urgency Cues in Kaba-Kaba Tourism Village, Bali - Ni Made Ayu Natih Widhiarini; Ida Ayu Etsa Pracintya; I Komang Angga Tria Saputra (International Journal of Management Science and Information Technology, 2026)
Digital platforms increasingly shape destination discovery, but the effectiveness of behavioral cues may differ between commercial tourism products and community-based cultural destinations. This study examines the effects of Scarcity Nudge, Urgency Nudge, and Fear of Missing Out (FOMO) on Generation Z's Visit Intention toward Kaba-Kaba Tourism Village, Bali. Using a between-subject quasi-experimental design, 120 active social media users aged 18-29 who had never visited the village were exposed to neutral, scarcity-based, or urgency-based digital promotional content. The visual format and destination information were standardized, while the textual cue was varied across conditions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Urgency Nudge had a positive and significant effect on Visit Intention (beta = 0.570, p < 0.001), whereas Scarcity Nudge (beta = 0.105, p = 0.315) and FOMO (beta = 0.121, p = 0.079) were not significant. FOMO also did not moderate either nudge-intention relationship. The findings show that Generation Z responded more strongly to credible time-bound opportunities than to limited-availability or social-pressure cues in this cultural tourism context. The study extends digital nudging research by demonstrating its destination-specific effectiveness and recommends that tourism village managers promote genuine limited-time cultural events, seasonal activities, and community-led experiences while avoiding artificial scarcity claims.